The role of biomarkers in modern endodontic diagnosis - Trishala; Pandey, Pragya; Bharti, Ramesh; Verma, Promila (International Journal of Research in Medical Sciences, 2026)
Biomarker-based diagnostics represent an emerging frontier in precision endodontics, offering biologically informed approaches for the detection, monitoring, and management of pulp inflammation. Unlike conventional pulp testing methods that rely on subjective pain responses or thermal/electrical stimuli, biomarkers provide objective molecular and cellular insights into pulp health. Various biological markers-such as cytokines (IL-1β, TNF-α), neuropeptides (Substance P, CGRP), matrix metalloproteinases, and microRNAs-demonstrate distinct profiles in reversible versus irreversible pulpitis, enabling early detection and targeted interventions. Clinical applications include non-invasive analysis of dentinal fluid, gingival crevicular fluid, and saliva, often combined with advanced biosensors and point-of-care devices to improve diagnostic accuracy. Innovations in omics technologies, microfluidics, and artificial intelligence facilitate high-throughput biomarker analysis and predictive modeling of disease progression. Despite promising developments, challenges remain in standardization, sensitivity, cost-effectiveness, and clinical translation. Ongoing research into longitudinal monitoring and multi-marker panels holds potential for personalized pulp therapy. As biomarker-guided diagnostics evolve, interdisciplinary collaboration will be essential to integrate molecular insights into routine endodontic practice, enhancing early intervention and patient-specific care.